To Jerusalem and Beyond Interdisciplinary Approaches to the Study of Latin Travel Literature, c.1200-1500 - Fischer, Susanna; Booth, Philip; Bauer, Martin M. (Das Mittelalter. Perspektiven mediävistischer Forschung. Beihefte, 2023)
With the expansion of trading routes, pilgrimage, and missionary endeavours in the 13th century, Latin travel literature emerged as a distinctive genre like never before. To highlight the importance of this genre, this volume outlines and explores current and future research trajectories with a focus on Latin travel literature from c. 1200-1500. Combining digital, codicological, literary, philological, and anthropological approaches the volume analyses the ways in which these texts were produced, distributed, received, read, and how they can be interpreted. It argues for the importance of re-evaluating these texts and revisiting their contents in light of new methodological and theoretical approaches.